Analisa Perbandingan Metode SAW, WP, dan Topsis Dalam Menentukan Keputusan Pemilihan Kostan Bagi Mahasiswa - Sultan Aji Saputra; Amaranullah Putra S.; Aryana Muhammad Primansyah; Zaisul Muttabi; Fadlan Fadillah; Perani Rosyani (CV. Multi Kreasi Media, 2023)
Kostan is a rental or temporary lodging that has several facilities available. Kost itself has a price determined by the owner of the kost and also various types of kost. Kostan is usually looking for someone to stay for a long time because it is far from the main house. Kostan is synonymous with the word Student because a student who has a house far from the campus or university needs a boarding house for temporary residence. In determining the boarding house they want to choose, students must look for some of the best boarding houses to determine. Starting from searching for information via the internet or coming directly to the place. One of the decisions to be chosen is to use a decision support system, where this system is part of a computer-based information system including knowledge-based that is used to support decision making in an organization. Where the system consists of various methods, such as the SAW, WP, and TOPSIS methods that we will use in determining this research. In this study, researchers used quantitative methods for their research, and for data collection methods researchers used observation, interviews, and literature studies. And with the aim of research, it will make it easier for students to be able to determine the best boarding house.